GROUNDS FOR REFUSING TO ENFORCE INTERNATIONAL ARBITRAL AWARDS UNDER THE NEW YORK CONVENTION: A REVIEW OF LAW AND PRACTICE (World Bulletin of Management and Law, 2023)
This article delves into the world of international arbitration and provides a brief review of the law and practice covering the grounds for refusing to recognise and enforce foreign or international arbitral awards under Article V of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958. Through a comprehensive analysis of court decisions from diverse jurisdictions, including the UK, the US, Uzbekistan and Europe, the article is intended to shed light on the nuances of interpretation and application of the grounds for refusal, including the invalidity of the arbitration agreement, incapacity of the party, procedural irregularities, the right to be heard, nonarbitrability and public policy. In this respect, a greater focus is given to the frequently-asserted and often-misunderstood issues such as the validity of arbitration agreements, arbitrability and public policy. This article also relies on the writings of legal thinkers who are well-known and highly qualified in the field of international arbitration so as to analyse and explain the refusal grounds of the Convention with more clarity. Overall, it seeks to contribute to the neverending debate over the Convention by analysing an important aspect of international dispute settlement that is of crucial importance to academics, practitioners and legislators.